Cost-Effectiveness Analysis of Combined Use of Oral Antihypertensive Outpatient Hypertension in Regional General Hospital Tugurejo Semarang Period 2007 - Timur, Willi Wahyu; Andayani, Tri Murti; Aribawa, Riyanta (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2012)
Background: Analysis of cost-effectiveness is an analysis which comparing therapy effective with its cost. In this research, therapies effective are compared between combination of oral anti-hypertension with cost that paid by patient. This research aims to identify the combination of oral anti-hypertension, which cost is the most costeffective on hypertension patient in RSUD Tugurejo Semarang, period 2007.Design and Methods: This research was a non-experimental using descriptive non-analytic, data collection performed in retrospective from medical record of patient of hypertension in RSUD Tugurejo Semarang, period 2007. Research subject was hypertension patient, which used two combinations that were anti-hypertension and using similar anti-hypertension, at least during 3-month period. Hypertension effective measured by calculating patient amount that blood pressure achieved the target during 2 month, after therapy performed. Cost effectiveness seen based on average cost-effectiveness ratio (ACER) value.Results: The result of analysis of cost-effectiveness using anti-hypertension on hypertension patient in RSUD Tugurejo Semarang, period 2007 for 44 cases has fulfilled the criterion. Female patients were 25 cases and male patients were 19 cases. The most used combination of oral anti-hypertension was class combination of diuretic-ACEI (angiotensin converting enzyme inhibitor) for 36,36%. Cheapest direct medical cost wascombination of ACEI–Beta blocker for Rp. 23.250,10. The biggest therapy effectiveness there was at combination of ACEI –diuretic for 46,88%.Conclusion: The most cost-effective is ACEI – diuretic with ACER value for 623,06 (Sains Medika, 4(2):124-133).